Japanese Language as an Organizational Barrier for International Students to Access to University Services: A Case of Aoyama Gakuin University - Hiratsuka, Hiroyoshi (Journal of International Students, 2016)
In 2011, Aoyama Gakuin University (AGU) started a government-funded degree program (taught in English) to accept international students with limited or no Japanese language proficiency. However, the students faced obstacles in accessing all of the university resources provided. In this article, I investigated Japanese language as an organizational barrier for students accessing to campus resources. I utilized the case study methodology through participatory observation on campus and face-to-face interviews.